Residence Time in Niches of Stagnant Flow Determines Fibrin Clot Formation in an Arterial Branching Model - Detailed Flow Analysis and Experimental Results - Reininger, Armin J; Reininger, Cornelia B; Heinzmann, Ulrich; Wurzinger, Laurenz J (Thrombosis and Haemostasis, 1995)
Deposition of blood components in branching flow has been investigated primarily with regard to platelets. We instead examined thrombin-induced fibrin clot formation in separated laminar as well as turbulent branching flow. The most rapid clot growth and largest clot mass was obtained at the lowest inflow rate. Increased inflow reduced the clot size and turbulence completely prevented clot formation. Examination of corresponding flow conditions revealed the recirculation zone in laminar flow to be characterized by two stationary, counterrotating vortices. Niches of stagnant flow, exhibiting long residence times, low wall shear rates and characterized by convergent flow, were spared between the bulk flow and these vortices. Here, fibrin clot growth continued even when shear rates were increased more than 100-fold. Our results indicate that, in branching flow, the long residence times and convergent flow characteristic of flow niches rather than shear rate are critical for fibrin clot formation.